Caracteriza????o da express??o g??nica de vias de transdu????o do sinal no mioc??rdio remoto ao infarto induzido por abla????o ventricular esquerda e oclus??o da art??ria coron??ria em ratos - Santana, Eduardo Tadeu (2015)
The ligation of the anterior descending coronary artery is the most commonly used experimental model to induce myocardial infarction (MI) in rodents. A high mortality in the acute phase and the heterogeneity of the size of the MI obtained are drawbacks recognized in this model. In an attempt to solve the problem, our group recently developed a new MI experimental model which is based on application of myocardial ablation radio-frequency currents (AB-RF) that yielded MI with homogeneous sizes and significantly reduce acute mortality. In addition, cardiac structural and functional changes aroused by AB-RF were similar to those seen in animals with MI induced by coronary artery ligation. Herein, we evaluated modifications of gene expression that govern post-MI milieu in occlusion and ablation models. We analyzed 48 mRNA expressions of 9 different signal transduction pathways (signs of cell survival and metabolism, matrix extracellular, cell cycle, oxidative stress, apoptosis, calcium signaling, hypertrophy markers, angiogenesis and inflammation) in rat left ventricle 1 week after MI promoted by either coronary occlusion and AB-RF. Furthermore, high-throughput miRNA analysis was also assessed after either MI procedures. Interestingly, mRNA expression levels and miRNA expressions were similar in both models after MI, with few specificities in each model. This study reports for the first time the global changes in rat cardiac mRNA and miRNA contents after two different MI procedures and identifies key signaling regulators modulating the pathophysiology of these two models that might culminate in heart failure. Furthermore, these analyses would enhance our present knowledge regarding altered pathophysiology of these two different MI models.